Diseño de un manual de procedimientos y funciones administrativos para la empresa distribuidora Jinzen de la ciudad de Quito de la Provincia de Pichincha. - Robalino Changoluisa, Erika Lorena (2015)
This project aims to design a manual of procedures and administrative functions for the company Distribuidora Jinzen city of Quito in the province of Pichincha; it has had a significant and noticeable growth in the field of import and trade; same that has positioned the company nationwide. The development of this project is done through direct observation; in which clearly determines the problem that arises within the company, for which the manual, detailing clearly, concisely is made: • Organizational structure • Organization Chart • Job profiles • Flow diagrams of the processes Improving the organizational level of the company, optimizing administrative control financial, economic and human resources; remove deadlocks in each process, increase customer satisfaction, growth of the company.